Global imbalances and the Chinese balance of payments - Hansjörg Herr (Intervention. European Journal of Economics and Economic Policies, 2009)
First paragraph: After the start of reform in 1978 China became one of the most successful developing countries in the world economically. China did not follow the philosophy of neoclassical development models upheld by the Washington Consensus and the savings-gap model. In fact, the Chinese miracle is unthinkable without a strong developmental state and the non-acceptance of long-term deficits in the current account. It is in keeping with the tradition of an Asian development model, as exemplified by Japan and later the smaller and bigger Asian tigers. One of the success factors of the Chinese miracle is the export orientation of the Chinese economy. Along with others, China became one of the countries with huge current account surpluses.
Keywords: 330